A novel functional infrared imaging system coupled with multiparametric computerised analysis for risk assessment of breast cancer. - Sella, Tamar; Sklair-Levy, Miri; Cohen, Maya; Rozin, Mona; Shapiro-Feinberg, Myra; Allweis, Tanir M; Libson, Eugene; Izhaky, David (European Radiology, 2013)
Objective: We evaluated a functional three-dimensional (3D) infrared imaging system (3DIRI) coupled with multiparametric computer analysis for risk assessment of breast cancer. The technique provides objective risk assessment for the presence of a malignant tumour based on automated parameters derived from a clinically known training set.Methods: Following institutional review board approval, we recruited 434 women for this prospective multicentre trial, including 256 healthy woman undergoing routine screening mammography with BI-RADS-1 results and 178 women with newly diagnosed breast cancer. This was a two-phase study: an initial training and calibration phase, followed by a two-armed blinded evaluation phase (52 healthy and 66 with breast cancer). 3DIRI data sets were acquired using a non-contact, no radiation system.Results: The sensitivity and specificity of functional infrared imaging in providing the correct risk for the presence of breast cancer were 90.9 % and 72.5 %, respectively. The area under the ROC curve was 86 %. Forty-two of the 60 (70 %) cancers in women correctly classified by the system as suspicious were smaller than 20 mm in size.Conclusion: The preliminary blinded results of this novel technology show sufficient performance of functional infrared imaging in providing risk assessment for breast cancer to warrant further clinical studies.Key Points: • 3D functional infrared imaging (3DIRI) provides new metabolic signatures from breast lesions. • 3DIRI offers high sensitivity for risk assessment of breast cancer. • It also has reasonable specificity. • This initial experience warrants further evaluation in larger clinical trials.